Application of Tensile Testing on Ulin Wood And Bungur Wood as Main Materials for 20 GT Traditional Fishing Vessel Hull - Arifuddin, Andi Mursid Nugraha; Alamsyah; Burliyanto, Decky; Suardi (Naval Architecture Departement, Hasanuddin University, 2023)
Fishing boats in North Penajam Paser are made by combining 2 types of wood in the hull. This combination of wood types is carried out to save the material procurement budget. Bungur wood is the alternative choice for shipyards for hull material combined with Ulin wood. For this reason, this paper shows the differences in the tensile strength performance of these 2 types of traditional wooden ship hull materials. The experimental method of destructive testing of the type of Tensile test was applied in this study. Where the experimental results show that the tensile strength of the crepe is 22% lower than the tensile strength of ulin wood. Meanwhile, in terms of stiffness, crepe wood is superior to ulin wood, where the difference reaches 22.22%. Bungur wood still has the potential to be used for wooden ships with an LoA (length over all) value of <15 meters or for ships that have a lower hydrostatic load than that which can be accepted by Bungur wood.